Effects of antibiotics on the viability of and toxin production by Clostridium botulinum. (8th September 2021) - Yutani, Masahiro; Matsumura, Takuhiro; Fujinaga, Yukako
Abstract: Clostridium botulinum causes infant and adult intestinal botulism by colonizing in the intestine and producing botulinum neurotoxin (BoNT). Antimicrobial agents are not currently used for treatment due to the potential facilitation of BoNT production and bacterial cell lysis, which releases toxins into the intestinal lumen. In this study, we analyzed effects of four antibiotics on the viability of and BoNT production by four C. botulinum group I strains. Our results indicate that metronidazole rapidly reduced their viability without enhancing BoNT production. Antibiotics with these properties may promote elimination of C. botulinum from the intestines while maintaining low levels of BoNT.